2020
DOI: 10.4236/jcc.2020.87005
|View full text |Cite
|
Sign up to set email alerts
|

Improvised Technique for Analyzing Data and Detecting Terrorist Attack Using Machine Learning Approach Based on Twitter Data

Abstract: Social media are interactive computer mediated technology that facilitates the sharing of information via virtual communities and networks. And Twitter is one of the most popular social media for social interaction and microblogging. This paper introduces an improved system model to analyze twitter data and detect terrorist attack event. In this model, a ternary search is used to find the weights of predefined keywords and the Aho-Corasick algorithm is applied to perform pattern matching and assign the weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 9 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…The most related works; using social media for terrorism prediction include [13], [14], and [15]. In [13], the NB algorithm is used, and the model performance is measured by precision, recall, and F-Measure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most related works; using social media for terrorism prediction include [13], [14], and [15]. In [13], the NB algorithm is used, and the model performance is measured by precision, recall, and F-Measure.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in [14], the purpose is to detect extremist-related tweets, and therefore not adequate for this project. Another related work in the area includes [15], where social media collected from Twitter (now X) are analyzed and correlated to past terrorist attacks. The difference between that research approach and ours is that we seek to predict future attacks, whereas [15] focuses on past attacks.…”
Section: Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…The study concluded that fake tweets' survival rate was far longer than the real ones. An efficient and accurate model for event detection is presented in [45] which used ternary search for finding the weight of the keywords used.…”
Section: Terrorist Attack Detection Methodsmentioning
confidence: 99%
“…This is because this kind of data are almost always classified or inappropriate for academic research [50][51][52][53][54][55]. Unlike most studies in this area, which rely on data from social media interactions [77][78][79][80][81][82][83][84][85][86][87][88][89][90][91], our work is grounded on real-world social ties among terrorists, namely physical face-to-face interactions. This kind of data is more reliable because social media interactions can be used for deliberately sharing false realities, aiming to mislead law enforcement agencies [92][93][94][95][96].…”
Section: Iterative Loopmentioning
confidence: 99%